"If You Don't Get Caught": Islands, Isolation, and Entrapment in Contemporary Scottish Women's Poetry. (31st December 2020) - Mackay, Peter
Abstract: This essay explores the trope of the island in recent Scottish poetry and in particular the tendency to treat poems as islands and vice versa. With a particular focus on the work of Meg Bateman, Jen Hadfield, Kathleen Jamie, Jackie Kay, and Liz Lochhead, the essay discusses ideas of entrapment, freedom, and isolation, to suggest that alongside the Utopian imaginings of islands, there is also the possibility of them becoming, like St Kilda for Lady Grange, constrictive prison cells.